MODELING AND INVESTIGATION OF THE OPERATION OF THE TEMPERATURE DIFFERENCE CONTROLLER IN THE MODE OF SCHEDULED COOLING IN THE REACTOR CONTROL SYSTEM - F.Z. Jamoldinov,; R.M. Abdullajonov, (International Journal of Innovations in Engineering Research and Technology, 2023)
This research work is dedicated to modeling and investigating the operation of the temperature difference regulator during planned cooling in the control system of the VVER-1000 reactor based on the software and technical complex of technological software and technical means. The mathematical model and transfer function of the control object, as well as coding algorithms for the executive mechanism, control object, and regulator, were developed in the work. The influence of the regulator on the quality of regulation was investigated.